PERAN GURU PPKn DALAM MENCEGAH KENAKALAN PESERTA DIDIK - diange, Ilham; Yunus, Rasyid; Nggilu, Ariyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the role of Civic Education (PPKn) teachers in preventing student delinquency at SMP Negeri 2 Telaga, focusing on two main aspects: instructional activities and the development of school culture through character education. A descriptive qualitative approach was employed, utilizing interviews, observations, and document analysis as data collection techniques. The findings reveal that PPKn teachers actively instill character values during both classroom instruction and school-wide activities such as flag ceremonies and discussions, fostering student engagement and a positive learning environment. Teachers play a strategic role in guiding students away from deviant behaviors and encouraging responsible conduct. However, a notable challenge arises from a subgroup of students who carry negative influences from outside the school environment, requiring more intensive intervention. Meanwhile, the school promotes a positive culture by offering weekly varied activities that provide opportunities for quieter or less active students to express themselves, thus building self-confidence and participation. The role of PPKn teachers extends beyond classroom instruction, making a significant contribution to shaping student character and establishing a school environment conducive to the prevention of delinquency. ABSTRAKPenelitian ini bertujuan untuk mengkaji peran guru Pendidikan Pancasila dan Kewarganegaraan (PPKn) dalam mencegah kenakalan peserta didik di SMP Negeri 2 Telaga, dengan fokus pada dua aspek utama: kegiatan pembelajaran dan pengembangan budaya sekolah melalui pendidikan karakter. Pendekatan yang digunakan adalah kualitatif deskriptif, dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru PPKn aktif membangun nilai-nilai karakter dalam pembelajaran dan kegiatan sekolah, termasuk apel dan diskusi kelas, yang mendorong keterlibatan serta sikap positif siswa. Guru juga memainkan peran strategis dalam menciptakan suasana belajar yang kondusif dan mengarahkan peserta didik untuk menjauhi perilaku menyimpang. Namun, tantangan muncul dari sekelompok siswa yang membawa pengaruh negatif dari luar sekolah, sehingga membutuhkan pendekatan lebih intensif. Di sisi lain, pengembangan budaya sekolah dilakukan dengan memberi ruang bagi siswa pendiam atau kurang aktif untuk mengekspresikan diri melalui kegiatan mingguan yang bervariasi, guna membangun kepercayaan diri dan keterlibatan mereka. Peran guru PPKn terbukti melampaui pengajaran di kelas, dengan kontribusi nyata dalam membentuk karakter dan ekosistem sekolah yang mendukung pencegahan kenakalan peserta didik.